1968
DOI: 10.1111/j.2042-7158.1968.tb09756.x
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism of phenobarbitone

Abstract: The polymorphism of phenobarbitone has been investigated using infrared spectroscopy, X-ray diffraction and differential scanning calorimetry. Eight crystalline modifications have been isolated and shown to have distinguishable infrared absorption spectra and X-ray powder diffraction patterns. Other forms were found to be present in mixed crystals and molecular compounds obtained from mixtures of phenobarbitone with other barbiturates. Differential thermograms of three forms of thialbarbitone are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Brandstatter-Kuhnert & Aepkers (1961,1962) decribed eleven forms, some of which were found only in mixed crystals with other barbiturates. In the present work ten forms were obtained, including two not mentioned by Brandstatter-Kuhnert & Aepkers, and the individual forms have already been described (Mesley, Clements, Flaherty & Goodhead, 1968). The consistent conversion of all of these to a single form presents Some difficulty.…”
Section: R J Mesley a N D R L Clementsmentioning
confidence: 96%
“…Brandstatter-Kuhnert & Aepkers (1961,1962) decribed eleven forms, some of which were found only in mixed crystals with other barbiturates. In the present work ten forms were obtained, including two not mentioned by Brandstatter-Kuhnert & Aepkers, and the individual forms have already been described (Mesley, Clements, Flaherty & Goodhead, 1968). The consistent conversion of all of these to a single form presents Some difficulty.…”
Section: R J Mesley a N D R L Clementsmentioning
confidence: 96%
“…However, this preparation proved to be unstable, and did not last long enough for single-crystal measurements to be made. Form XIII was originally reported as a polymorph of phenobarbitone by Cleverley & Williams (1959), and called by them form V. It is unusual among drug barbituric acids in showing absorption bands in the infrared near 3500 cm -1, which were attributed to some degree of enolization in the pyrimidine ring by Cleverley & Williams (1959), and by Mesley et al (1968). Mesley et al also considered the possibility that these absorption bands resulted from the presence of water of crystallization, but rejected this hypothesis in favour of enolization.…”
Section: Polymorphs Of Phenobarbitonementioning
confidence: 96%
“…Thus, this form should strictly be excluded from the list of known polymorphs of phenobarbitone. It seems likely that form XII of phenobarbitone (Mesley et al, 1968) and form III of thialbarbitone (Kemithal, 5-alkyl, 5-AZ-cyclohexenyl barbituric acid) (Cleverley & Williams, 1959), both of which also show O-H stretching bands in the infrared, are also hydrates.…”
Section: Polymorphs Of Phenobarbitonementioning
confidence: 99%
“…Theophylline-Phenobarbital- Figure 6 is the phase diagram for Others (26,27) have reported that polymorphism in phenobarbital is sensitive to conditions of heating, and to the presence of other substances. Mesley (27) lists melting points of 13 phenobarbital polymorphs, including Form 111, 167"; Form N, 163"; Form V, 160'; andFormV1,157O.…”
Section: Resultsmentioning
confidence: 99%